CONTINUING EDUCATION IN NIGERIA (MEANING, OBJECTIVES, FORMS AND PROSPECTS) - Muhammad Shehu Hussain; Abdullahi Umar Alhassan; Isah Nahoga Kamba (European Scientific Journal, ESJ, 2013)
The idea of Continuing education suggests that something is missing that ought to be filled in, therefore the contemporary notion of education goes beyond what only take place in the four walls of the classroom. Continuing education connotes that sub-set of adult education that seeks to positively link the needs and aspirations of individuals with educational activities, for development of their potentialities and for the socioeconomic and political development of a nation or state. The paper examined the concepts of continuing education, objectives, forms, contents and challenges of continuing education and also highlighted the prospects that a nation or individuals can derive or achieve through the sustained impact of continuing education.